2011
DOI: 10.1021/ic200977n
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium Complexes of Thiaporphyrin and Dithiaporphyrin

Abstract: Successful synthesis and characterization of the six-coordinated complex [Ru(STTP)(CO)Cl] (1; STTP = 5,10,15,20-tetratolyl-21-thiaporphyrinato) allowed the development of the coordination chemistry of ruthenium-thiaporphyrin through dechlorination and metathesis reactions. Accordingly, [Ru(II)(STTP)(CO)X] (X = NO(3)(-) (2), NO(2)(-) (3), and N(3)(-) (4)) was synthesized and analyzed by single-crystal X-ray structural determination and NMR, UV-vis, and FT-IR spectroscopic methods. An independent reaction of STP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 42 publications
1
30
1
Order By: Relevance
“…However, 21-thiaporphyrin has been shown to form four, five and six coordinate metal complexes. [5][6][7][8][9] In all metallothiaporphyrin complexes, the thiophene ring is sharply bent out of the mean plane and binds to the metal in a η 1 (S)-fashion. Interestingly, the coordination chemistry of 21-selenoporphyrin has remained elusive although one expects that 21-selenoporphyrin also prefer to form metal complexes like 21-thiaporphyrin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, 21-thiaporphyrin has been shown to form four, five and six coordinate metal complexes. [5][6][7][8][9] In all metallothiaporphyrin complexes, the thiophene ring is sharply bent out of the mean plane and binds to the metal in a η 1 (S)-fashion. Interestingly, the coordination chemistry of 21-selenoporphyrin has remained elusive although one expects that 21-selenoporphyrin also prefer to form metal complexes like 21-thiaporphyrin.…”
Section: Resultsmentioning
confidence: 99%
“…However, among 21-heteroporphyrins, the metal coordination chemistry of 21-thia and 21oxaporphyrins is relatively well developed. Grażyński et al and others have shown that 21-thiaporphyrin forms coordinate complexes with Fe(II), 5a Ni(II), 5a Cu(II), 5b,c Pd(II), 5e Rh(III), 5f Li(I), 6 Hg(II) 7 and Ru(II) 9 whereas 21-oxaporphyrin forms complexes with Ni(II), 10 Co(II), 11 Mn(II), 11 Zn(II), 11,12 Cu(II) 13 and Fe(II). 14 The metal coordination chemistry of other heteroporphyrins such as 21-selenaporphyrins and 21-telluraporphyrins has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…13 It has been shown in the literature that Ru(II) porphyrin is one of the most important metalloporphyrin building blocks which is involved in construction of several non-covalent porphyrin arrays. 2 Interestingly, although Ru(II) complexes of 21-thiaporphyrin 43 and 21,23-dithiaporphyrin 44 were reported in the literature, no thiaporphyrin-based self assembled porphyrin oligomers were synthesized. However the free base thiaporphyrins containing meso-pyridyl and meso-hydroxyphenyl groups were used We reported the synthesis of unsymmetrical non-covalent dyads 65a-65d assembled using Ru-pyridine "N" interactions.…”
Section: Non-covalent Dyadsmentioning
confidence: 99%
“…22 Although these thiaporphyrins possess interesting optical properties, surprisingly their use in DSSCs is very uncommon. 23 Following our interest in thiaporphyrins and their metal complexes, 24,25 we have recently shown that these heteroporphyrins can be successfully applied as sensitizers in DSSCs. 26,27 Thiaporphyrin N3S-ECA, with an ethynylphenyl linker at a meso position and a carboxylic acid as the terminal anchoring group, gave very low efficiency with an iodine/triiodide redox electrolyte.…”
Section: Introductionmentioning
confidence: 99%